2014
DOI: 10.3390/s141223419
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Receptors for Bioanalyte Detection by Quartz Crystal Microbalances — From Molecules to Cells

Abstract: A universal label-free detection of bioanalytes can be performed with biomimetic quartz crystal microbalance (QCM) coatings prepared by imprinting strategies. Bulk imprinting was used to detect the endocrine disrupting chemicals (EDCs) known as estradiols. The estrogen 17β-estradiol is one of the most potent EDCs, even at very low concentrations. A highly sensitive, selective and robust QCM sensor was fabricated for real time monitoring of 17β-estradiol in water samples by using molecular imprinted polyurethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 69 publications
0
28
0
Order By: Relevance
“…Separately, they developed a surface-imprinted polyurethane nanolayer through the double imprinting approach, to generate selective interaction sites for bacterial recognition, even in complex matrices such as growth media. They reaffirmed that molecular imprinting is a versatile method for designing artificial receptors not only for small molecules, but also for larger analytes like bacteria cells (Latif et al, 2014). Buchegger et al (2014) combined ready-to-use resist with surface imprinting and UV-and thermo-nanoimprinting techniques to create a specific bacterial recognition layer by imprinting lipopolysaccharide (LPS) and lipoteichoic acid (LTA), instead of the whole bacteria cell.…”
Section: Mips As Quenchers In Sersmentioning
confidence: 93%
See 1 more Smart Citation
“…Separately, they developed a surface-imprinted polyurethane nanolayer through the double imprinting approach, to generate selective interaction sites for bacterial recognition, even in complex matrices such as growth media. They reaffirmed that molecular imprinting is a versatile method for designing artificial receptors not only for small molecules, but also for larger analytes like bacteria cells (Latif et al, 2014). Buchegger et al (2014) combined ready-to-use resist with surface imprinting and UV-and thermo-nanoimprinting techniques to create a specific bacterial recognition layer by imprinting lipopolysaccharide (LPS) and lipoteichoic acid (LTA), instead of the whole bacteria cell.…”
Section: Mips As Quenchers In Sersmentioning
confidence: 93%
“…They reported that the presence of an interconnected porous network through the MIP nanofilm improved recognition ability and substantially enhanced the sensitivity of the chemosensor (Suriyanarayanan et al, 2013). Latif et al (2014) reported a biomimetic QCM coating produced via two different imprinting strategies, for label-free detection of bioanalytes varying from endocrine disrupting chemicals to bacteria. They applied bulk imprinting to develop a highly sensitive, selective and robust QCM sensor for real-time estradiol monitoring, while investigating the effects of porogen and crosslinker for creation of an imprinted polyurethane nanolayer.…”
Section: Mips As Quenchers In Sersmentioning
confidence: 99%
“…Latif et al [25] used a bulk imprinting technique for the detection of the estradiols which are a kind of endocrine disrupting chemicals (EDCs). To achieve highly sensitive and selective detection even in the presence of very similar compounds that have nearly same structure, they used 17β-estradiol (E2) as a template.…”
Section: Mip Based-quartz Crystal Microbalance (Qcm) Sensorsmentioning
confidence: 99%
“…Its widespread usage, especially in these food contact materials, has inevitably lead to its exposure to human beings via food and drinking water [2,3]. As an endocrine-disrupting chemical (EDC) [4,5], it can destroy natural or synthetic compounds with endocrine function by simulating or blocking endogenous hormones [6]. To date, a temporary tolerable daily intake (t-TDI) of 4 µg kg −1 b.w.…”
Section: Introductionmentioning
confidence: 99%